Report on Proceedings of the Tenth Annual European CME Forum, Dublin, Ireland, November 2017. Issue 1 (1st January 2018) - Murray, Ron
ABSTRACT: The august setting of the Royal College of Physicians of Ireland saw participants from 17 different countries assemble for the Tenth European CME Forum between 8th and 10th November 2017. The main themes of the meeting were classified under the headings Inward (Educational design), Outward (Listening to others) and Onward (Collaborations and partnerships) addressed via a combination of presentations, interactive workshops, posters, and panel discussions. Topics explored included team engagement, the voice of the patient, harmonisation in European accreditation, competencies for CME professionals, and publishing in CME. Discussion evoked both consensus and contention and provided participants with excellent networking opportunities moving forward to the next decade of Forum meetings.